Analisis Pengaruh Corporate Social Responsibility (CSR) Terhadap Profitabilitas (Studi Kasus Pada PT Adaro Energy Tbk) - Maulana, Teguh Ari; Rithy, Sokchea (Journal of Economics and Management, 2023)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on financial performance, as measured by Return on Assets (ROA) and Return on Equity (ROE), at PT Adaro Energy Tbk. The research employs a quantitative approach using simple linear regression analysis to identify the relationship between CSR as the independent variable and ROA and ROE as dependent variables. Data processing and hypothesis testing were conducted using SPSS version 20. The empirical results indicate that CSR has a significant negative effect on ROA, where a 1% significant increase in CSR is associated with a 9.7% decrease in ROA. This finding suggests that higher CSR expenditure may reduce short-term asset efficiency. Conversely, CSR shows a positive and significant effect on ROE, where a 1.5% significant increase in CSR leads to a 3.7% increase in ROE, indicating that CSR implementation may enhance shareholder value. Overall, the results imply that CSR influences financial performance differently depending on the profitability indicator used.